2022
DOI: 10.3390/agronomy12051102
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Aqueous and Ethanolic Extracts of Coconut (Cocos nucifera) Fruit By-Products

Abstract: Coconut is widely used as a food source in producing countries, and during consumption, the waste that is generated needs to be reduced through by-products processing to ensure environmental sustainability. This study aimed to assess the functionality of by-products (endo- and mesocarp) of coconuts at early and mature stages. The aqueous and ethanolic (50 and 100% ethanol in water) extracts of coconut by-products were evaluated for the DPPH radical scavenging activity and subjected to linoleic acid-β-carotene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Even, Pearson correlation analysis suggested a strong positive correlation between antioxidant activity of CKE with TPC (DPPH, R 2 = 0.87; H 2 O 2 , R 2 = 0.68) and TFC (DPPH, R 2 = 0.77; H 2 O 2 , R 2 = 0.77). Our findings are consistent with earlier research showing a co-relation between antioxidant activity and phenolic and flavonoid compounds in a number of locally produced herbal extracts [ 74 ] and coconut fruit extract [ 75 ]. Additionally, we looked into the acute oral toxicity effect of CKE in accordance with the acute oral toxicity OECD/OCED (423) guidelines in order to assess the maximum dose limit of CKE in vivo [ 51 , 76 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Even, Pearson correlation analysis suggested a strong positive correlation between antioxidant activity of CKE with TPC (DPPH, R 2 = 0.87; H 2 O 2 , R 2 = 0.68) and TFC (DPPH, R 2 = 0.77; H 2 O 2 , R 2 = 0.77). Our findings are consistent with earlier research showing a co-relation between antioxidant activity and phenolic and flavonoid compounds in a number of locally produced herbal extracts [ 74 ] and coconut fruit extract [ 75 ]. Additionally, we looked into the acute oral toxicity effect of CKE in accordance with the acute oral toxicity OECD/OCED (423) guidelines in order to assess the maximum dose limit of CKE in vivo [ 51 , 76 ].…”
Section: Resultssupporting
confidence: 93%
“…2 G). According to these findings, there may be a correlation between the antioxidant activity and phenolic/flavonoid compounds of CKE, as suggested by yeni et al, 2021 and Leliana et al, 2022 [ 74 , 75 ]. Moreover, during in vivo acute oral toxicity studies, CKE demonstrated non-toxicity up to 2000 mg/kg body weight in mice.…”
Section: Discussionmentioning
confidence: 69%
“…Coconut, a fruit with an annual world production of 62.41 million tons, is an important source of lignocellulosic material [10]. The endocarp (inner shell part), mesocarp (fibrous part), and exocarp (outer shell) of coconut comprise about 60% of total fruit weight and are residues with high lignin and cellulose content that can be valorized as material for sustainable bioenergy and bioproducts [11,12]. However, coconut processing industries primarily focus on extracting coconut meat to produce oil, desiccated coconut, coconut milk, and other derivatives, as well as commercializing fresh coconut for water consumption.…”
Section: Introductionmentioning
confidence: 99%
“…According to Leliana et al [4] coconut by-product extracts, particularly the immature mesocarp, can be used as an alternative natural antioxidant. Coconut water has the potential to have a substantial impact on human health due to its pharmacological activities as well as plant growth and development in vitro propagation [1].…”
Section: Introductionmentioning
confidence: 99%